Histoplasmose infecção em pacientes HIV/AIDS residentes na cidade de Fortaleza, Ceará - Bezerra, Fabricia Salvador (2009)
Histoplasmosis is an infection disease caused by the fungus Histoplasma capsulatum var. capsulatum that can affect humans and several other animal. This fungus can be found in nature, mainly in places rich in bat and bird droppings: dirty and abandoned chicken coops, cave environments, old constructions, building domes and hollow trees. The infection in humans occurs through the upper airways. Since the HIV outbreak in the 1980s, it is noticed an increasing detection of disseminated histoplasmosis among aids patients assisted in reference clinics of Fortaleza, suggesting the Brazilian State of Ceará as an area with high endemicity related to this fungus. The purpose of this study is to identify histoplasmosis infection prevalence among HIV/aids-infected patients, who live in the city of Fortaleza, Ceará. It is a transverse, descriptive and analytic study, with a sample of 161 patients observed at the HIV/aids ambulatory from José de Alencar Center of Medical Specialties, and when invited, agreed to participate. For this, they filled in a form, took an intradermal test with histoplasmin (mycelial phase, provided by Fiocruz – RJ), and had their blood collected to serology via immunodiffusion (commercial antigens and antibodies from Histoplasma capsulatum and Coccidioides immitis were provided by Immy Immunodiagnostics laboratory). The general characterization of patients revealed that, on average, most participants were 35,11 years old, men (76,40%; n=123), single (67,70%, n=109), with a maximum family income of three minimum salaries (81,99%; n=132), and having more than 10 years of education (44,10%; n=71). Their previous employment situation had a variable distribution, although the majority of the group is currently unemployed. A number of 137 patients (85,10%) live in houses, and Messejana was the most informed quarter by the participants (8,7%; n=14). The year of 2008 had the most frequent HIV diagnoses among patients, with 66,46% (n=107). The prevalence of histoplasmosis infection among HIV/aids-infected patients, who live in the city of Fortaleza, was 12,42%. Some variables, such as the presence of chicken coops in the patient’s current neighborhood (p=0,031), the presence of mango trees in the current residence (p=0,023), dealing with soil in the past (p=0,021) and visiting small farms in the past (p=0,009) proved to be significant to the Histoplasma infection. However, the use of antiretroviral medication and having or not AIDS did not influence the reactivity to histoplasmin (both p=1,000). It can be concluded that Fortaleza constitutes an area with significant prevalence of histoplasmosis infection, considering that the analyzed population referred to people with suppression of the immune response. This result points out the necessity of identifying patients at risk for histoplasmosis, and also of implementing prophylactic measures on those susceptible to the severe forms of this disease.